Executive Committee Minutes 2014-12-04 - Academic Senate:::::::::
Agenda – Approved. Minutes of 11/13 – Approved. Chair Report. Question for the President. Provost Report. Statewide Senator Report. Request for Posthumous Degree for Kayla Chesser approved for the Senate's consent calendar. Vice Chair Report. Global Studies Major and Minor revisions approved for the Senate's consent calendar. Cultural Resources Management revisions approved for the Senate's consent calendar. Vice President of Administration and Finance Report. From FSAC: Interim criteria for implementing article 20.37 approved. Associated Students Report. GMC Director of Popular Programming and Director of Development search committees. EPC Report. FSAC Report. SAC Report. CFA Report. Union protestors invited to the Senate not approved. Ex Com Rep to the SEC Report. Senate agenda approved. Good of the Order: Resolution Expressing Appreciation and Best Wishes to Vice Chair Terry Lease – approved by acclimation